Response Calls Evoked by Playback of Natural 50-kHz Ultrasonic Vocalizations in Rats - Berz, Annuska C.; Wöhr, Markus; Schwarting, Rainer K. W. (Frontiers in Behavioral Neuroscience, 2022)
Rats are highly social animals known to communicate with ultrasonic vocalizations (USV) of different frequencies. Calls around 50 kHz are thought to represent a positive affective state, whereas calls around 22 kHz are believed to serve as alarm or distress calls. During playback of natural 50-kHz USV, rats show a reliable and strong social approach response towards the sound source. While this response has been studied in great detail in numerous publications, little is known about the emission of USV in response to natural 50-kHz USV playback. To close this gap, we capitalized on three data sets previously obtained and analyzed USV evoked by natural 50-kHz USV playback in male juvenile rats. We compared different rat stocks, namely Wistar and Sprague-Dawley and investigated the pharmacological treatment with the dopaminergic D2 receptor antagonist haloperidol. These response calls were found to vary broadly inter-individually in numbers, mean peak frequencies, durations and frequency modulations. Despite the large variability, the results showed no major differences between experimental conditions regarding call likelihood or call parameters, representing a robust phenomenon. However, most response calls had clearly lower frequencies and were longer than typical 50-kHz calls, i.e., around 30 kHz and lasting generally around 0.3 s. These calls resemble aversive 22-kHz USV of adult rats but were of higher frequencies and shorter durations. Moreover, blockade of dopamine D2 receptors did not substantially affect the emission of response calls suggesting that they are not dependent on the D2 receptor function. Taken together, this study provides a detailed analysis of response calls towards playback of 50-kHz USV in juvenile Wistar and Sprague-Dawley rats. This includes calls representing 50-kHz USV, but mostly calls with lower frequencies that are not clearly categorizable within the so far known two main groups of USV in adult rats. We discuss the possible functions of these response calls addressing their communicative functions like contact or appeasing calls, and whether they may reflect a state of frustration. In future studies, response calls might also serve as a new read-out in rat models for neuropsychiatric disorders, where acoustic communication is impaired, such as autism spectrum disorder.